High prevalence of Plasmodium falciparum gametocyte infections in school-age children using molecular detection: patterns and predictors of risk from a cross-sectional study in southern Malawi. (December 2016) - Coalson, Jenna; Walldorf, Jenny; Cohee, Lauren; Ismail, Miriam; Mathanga, Don; Cordy, Regina; Marti, Matthias; Taylor, Terrie; Seydel, Karl; Laufer, Miriam; Wilson, Mark
Abstract Background In endemic areas, many people experience asymptomaticPlasmodium infections, particularly older children and adults, but their transmission contribution is unknown. Though not the exclusive determinant of infectiousness, transmission from humans to mosquitoes requires blood meals containing gametocytes. Gametocytes often occur at submicroscopic densities, challenging measurement in human populations. More sensitive molecular techniques allow better characterization of gametocyte epidemiologic patterns. Methods Approximately 30 households were selected from each of eight sites in southern Malawi during two cross-sectional surveys. Blood was sampled from 623 people during the dry season and 896 the following rainy season. Among people PCR-positive forPlasmodium falciparum, mature gametocytes were detected by qRT-PCR. Regression models evaluated predictors of gametocyte carriage and density in the total population and among those with PCR-positive infections. Results The prevalence of gametocyte carriage by molecular testing was 3.5% during the dry season and 8.6% during the rainy season, and by microscopy 0.8 and 3.3%, respectively. Nearly half of PCR-positive infections carried gametocytes, regardless of recent symptom status. AmongP. falciparum -infected people, only living in unfinished houses and age were significantly associated with gametocyte presence. Infected people in unfinished houses had higher odds of carrying gametocytes (OR 2.24, 95% CI 1.16–4.31), and 31% (95% CI 3–65%) higher gametocyte density than those in finished houses. School-age children (5–15 years), had higher odds than adults (≥16 years) of having gametocytes when infected (OR 2.77, 95% CI 1.47–5.19), but 31% (95% CI 11–47%) lower gametocyte density. Children <5 years did not have significantly higher odds of gametocyte carriage or density when infected than adults. Conclusions School-age children frequently carry gametocytes in communities of southern Malawi and represent an under-recognized reservoir of infection. Malaria elimination strategies should address these frequently asymptomatic reservoirs, especially in highly endemic areas. Improved household construction may also reduce the infectious reservoir.